Caracterización dendrologica de las especies forestales maderables en la microcuenca de la quebrada Pabloyacu - Moyobamba- San Martin - Aguila Cobos, Hanleth Del (2010)
This research study was conducted in the sector "Pabloyacu" located in the district and province of Moyobamba, Department of San Martín Peru, aiming to evaluate the characteristics of trees from forest timber species predominant in the watershed of the creek Pabloyacu, as this will contribute to existing knowledge ofthe flora in the area. We identified 40 species were grouped into 25 botanical families. The family Moraceae (6 species) was the most named. lt is followed by Arecaceae (5 species), then there is the family Lauraceae (3 species), t hen the family Melastomataceae, Tiliaceae, Sapotaceae, Vochysiaceae with 2 spec ies each, and Anacardiaceae, Apocynaceae Araliaceae, Bignoniaceae, Boraginaceae, Burceraceae, Cecropiaceae, Euphorbiaceae Fabaceae, Flacourtiaceae, Malpighiaceae, Miliaceae, Myristicaceae, Olacaceae, Phyl lanthaceae, -Polygonaceae, Ulmaceae Urticaceae were represented by one species each. Through the importance value index shows five most important from the ecological point of view because it shows us that have weight organic species by their dominance, abundance and often to regenerate these types of areas, since the study area has been tampered with, today this is in the process of regeneration and primary forest transition to the floristic composition is present. lt is therefore advisable when carrying out reforestation of river basins, watersheds, establishing systems of forest plantations with native species found in the area, through the implementation of efficient and competitive technologies and systems capable of achieving average rates of return and appropriate forest productivity and simultaneously contribute to the recovery of soils and the economic and social development oflocal people.